MAQASID AL-SHARIAH VALUES ON MANAGING ASSETS IN THE INDONESIAN MUSLIM MERCHANT ASSOCIATION (ISMI) EAST JAVA PERSPECTIVE - Ika Khusnia Anggraini (Al Qalam, 2020)
Indonesia is a country with the largest Muslim population who are the actors of various types of economic practices in this modern era. However, fiqh products is not able to answer all of problems in modern economic activities. So we need an alternative and solution amid the high stretching of Muslim entrepreneurs who want to migrate to sharia-based business activities. Maqasid al-Sharia is a principle in Islamic law which is expected to be able to solve these problems. Asset management is the object of this research as a way to fully and broadly understand the implementation of sharia values in economic and business activities. This research was conducted qualitatively with a phenomenological approach. The results of this study indicate that there is a strong relationship in the implementation of Maqasid al-Sharia values on asset management of ISMI East Java members both theoretically and practically. The type of asset management that uses the Islamic Wealth Management (IWM) approach has all the indicators in Maqasid al-Muamalah which include al-rawaj, al-wudluh, al-hifzh, al-tsabat and al-'adl. As for the presence of ISMI as an entity that accommodates Muslim entrepreneurs with the same goal of reviving the spirit of Islam in a congregation has many benefits. Among these benefits are educational benefits, networking benefits and social benefits. ISMI East Java as an educational forum for members in studying Islamic economics and business and progressive business development with the involvement of technology. ISMI East Java is also a forum for friendship and productive discussions that create opportunities in the form of cooperation (syirkah). From a social aspect, ISMI East Java also has activities around ZISWAF as a manifest of Islamic philanthropy in distributing assets to people in need.